FARMERS KNOWLEDGE LEVEL IN SINJAR DISTRICT / NINEVEH GOVERNORATE IN THE FIELDS OF USING CROP ROTATIONS AND ITS RELATIONSHIP WITH SOME FACTORS - Radwan T. AL-Kashab (Mesopotamia Journal of Agriculture)
The objectives of this research were to determine the farmers knowledge level in Sinjar District / Nineveh Governorate in the fields of crop rotations, and to determine farmers knowledge level in each field and item, also to find out the differences of farmers knowledge according to some factors, and to determine the relationship between the degree of knowledge and a set of independent factors. The research sample included 72 respondents. The data were collected through an interview. Special questionnaire has been developed to estimate farmers knowledge level by using test method after testing the validity and reliability of the questionnaire. Percentage weight, arithmetic mean, analysis of variance and multiple step-wise regression analysis were used in analyzing the data. It was found that 52.778% of the respondents were of medium knowledge level in using crop rotations. The highest knowledge level of respondents were in the field of maintaining soil fertility. Also there were significant differences in the degree of farmers knowledge according to: age, education level, type of land tenure number of years using crop rotations, desire for renewal and previous training. While there were no significant differences according to: social statue and sources of information. Also it was found that the factor number of years using crop rotations explained 29.542% of the variation degree of farmers knowledge level.